2021
DOI: 10.1111/and.14169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wuzi Yanzong Pills on Sertoli cells and blood–testis barrier in heat‐stressed rats based on Akt signalling pathway

Abstract: The blood–testis barrier (BTB) of Sertoli cells (SCs) is an important biological barrier that maintains spermatogenesis and provides a favourable microenvironment for spermatogenesis. However, heat stress can directly damage the BTB structural proteins of testicular SCs, leading to dyszoospermia. Wuzi Yanzong Pills (WYP) is a traditional Chinese medicine formula used to treat male reproductive diseases. However, whether WYP could ameliorate heat stress injury in primary SCs extracted from rat testes and BTB pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Therefore, maintaining BTB integrity is an important basis for normal spermatogenesis. Fortunately, some drugs, such as Lycium barbarum polysaccharide [ 43 ] and traditional Chinese medicine [ 44 , 45 ], have been found to maintain BTB integrity and promote spermatogenesis. In this study, we confirmed that ALKBH5 in Sertoli cells is involved in regulating BTB integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, maintaining BTB integrity is an important basis for normal spermatogenesis. Fortunately, some drugs, such as Lycium barbarum polysaccharide [ 43 ] and traditional Chinese medicine [ 44 , 45 ], have been found to maintain BTB integrity and promote spermatogenesis. In this study, we confirmed that ALKBH5 in Sertoli cells is involved in regulating BTB integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Wu‐Zi‐Yan‐Zong‐Wan may ameliorate BTB dysfunction by regulating proinflammatory cytokine levels 38,39 . Icariina prevents the degradation of gap junction intercellular communication and impairment of connexin 43 in the BTB that are induced by microcystin‐leucine‐arginine 40 . Lycium barbarum polysaccharide can ameliorate the damage to the structural integrity of the BTB induced by heat stress 41 .…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Icariina prevents the degradation of gap junction intercellular communication and impairment of connexin 43 in the BTB that are induced by microcystin-leucine-arginine. 40 Lycium barbarum polysaccharide can ameliorate the damage to the structural integrity of the BTB induced by heat stress. 41 QJP can upregulate the PI3K/Akt/Rictor signaling pathway by altering p-Akt/t-Akt, PI3K p85α, PI3K 110β and Rictor expression.…”
Section: Qjp Prevented Cdcl 2 -Induced Testicular Injury In Micementioning
confidence: 99%
“…Studies have shown that WZYZP has a developmental and proliferative effect on supporting cells in both physiological and pathological states in mice and rats and can promote male reproductive function by potentially activating the Akt signaling pathway. [55,56] Zhang et al [57] found that WZYZP-containing serum promoted supporting cell viability in normal rats. Furthermore, WZYZP is capable of repairing damaged supporting cell cytoskeleton, regulating their expression, promoting supporting cell differentiation and maturation, and governing the secretory function of supporting cells, thereby inhibiting the apoptosis of spermatogenic cells.…”
Section: Experimental Animal/cell Studies On Pharmacological Effects ...mentioning
confidence: 99%
“…Wuzi Yanzong pill has been implicated in the regulation of several signaling pathways. Wuzi Yanzong pill promotes Akt phosphorylation, thereby promoting supporting cell differentiation [56] and proliferation [55] by activating Akt signaling pathway, improving BTB protein damaged by heat stress, and subsequently improving spermatogenesis disorders. [56] Furthermore, studies have shown that WZYZP ameliorates testicular heat stress–induced spermatogenesis disorder by regulating Akt and nuclear factor κB (NF-κB) signaling pathways.…”
Section: Experimental Animal/cell Studies On Pharmacological Effects ...mentioning
confidence: 99%